2011
DOI: 10.1111/j.1095-8649.2011.02989.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of paternal nutrient provisioning to embryos in broad‐nosed pipefish Syngnathus typhle

Abstract: In two experiments, radioactively labelled nutrients (either (3)H-labelled amino-acid mixture or (14)C-labelled glucose) were tube-fed to brooding male Syngnathus typhle. Both nutrients were taken up by the males and radioactivity generally increased in the brood pouch tissue with time. Furthermore, a low but significant increase of (3)H-labelled amino acids in embryos was found over the experimental interval (48 h), whereas in the (14)C-glucose experiment the radioactivity was taken up by the embryos but did … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
51
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(54 citation statements)
references
References 39 publications
3
51
0
Order By: Relevance
“…These results highlight a potential O 2 limitation to brooding within the closed environment of the brood pouch. The evolution of the brood pouch among syngnathids has been conceptually linked to more advanced types of care because of the potential to osmoregulate (Quast and Howe, 1980;Carcupino et al, 1997Carcupino et al, , 2002Partridge et al, 2007;Ripley, 2009) and to provide nutrients (Haresign and Shumway, 1981;Ripley andForan, 2006, 2009;Kvarnemo et al, 2011) to the developing youngabilities that are limited in species that do not have brood pouches (Berglund et al, 1986b;Carcupino et al, 2002). Therefore, it is important to note that, in terms of oxygenation, the presence of a brood pouch is here shown to limit, not ease, embryo access to O 2 and thus limit their development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results highlight a potential O 2 limitation to brooding within the closed environment of the brood pouch. The evolution of the brood pouch among syngnathids has been conceptually linked to more advanced types of care because of the potential to osmoregulate (Quast and Howe, 1980;Carcupino et al, 1997Carcupino et al, , 2002Partridge et al, 2007;Ripley, 2009) and to provide nutrients (Haresign and Shumway, 1981;Ripley andForan, 2006, 2009;Kvarnemo et al, 2011) to the developing youngabilities that are limited in species that do not have brood pouches (Berglund et al, 1986b;Carcupino et al, 2002). Therefore, it is important to note that, in terms of oxygenation, the presence of a brood pouch is here shown to limit, not ease, embryo access to O 2 and thus limit their development.…”
Section: Discussionmentioning
confidence: 99%
“…More complex brood pouches enable males to physically protect the embryos from external factors such as predators, and to provision them with nutrients, osmoregulation and oxygenation during brooding (Wilson et al, 2001). Male provisioning of nutrients to the developing young has been shown in a number of pipefish species (Haresign and Shumway, 1981;Ripley andForan, 2006, 2009;Kvarnemo et al, 2011). Also, the function of the brood pouch in osmoregulation is well established (Quast and Howe, 1980;Carcupino et al, 1997;Partridge et al, 2007;Ripley, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…1986b; Ripley and Foran 2006; Ripley 2009; Kvarnemo et al. 2011). Furthermore, species with enclosed brood pouches (e.g., Syngnathus spp.…”
Section: Introductionmentioning
confidence: 99%
“…Together with the fact that it provides extensive parental care and lives in an environment with naturally high variability in O 2 levels [38 -41], these characteristics make it a very apt model organism. As is typical for many pipefishes and seahorses (Syngnathidae), males of this genus care for the developing embryos in a sealed brood pouch where they protect, osmoregulate, oxygenate and transfer nutrients to the embryos through the vascularized walls of the pouch [37,[42][43][44][45]. Moreover, previous work on S. typhle has shown that larger embryos have higher respiration rates than smaller ones [46], larger eggs result in larger offspring [47] and that larger juveniles enjoy fitness benefits [48].…”
Section: Introductionmentioning
confidence: 99%